Loss of Phosphatase and Tensin Homologue (PTEN) Expression Associated with Higher Risk Grade Group Gleason Prostate Adenocarcinoma in Sanglah Hospital Denpasar - Tjandra Kristiana; I Gusti Ayu Sri Mahendra Dewi; Luh Putu Iin Indrayani Maker; Herman Saputra; Ni Putu Sriwidyani; I Made Muliarta (National Cancer Center - Dharmais Cancer Hospital, 2019)
Background: Prostate cancer is the second most common malignancy in men and the fifth most common cause of death worldwide. In Asia, 59.3% of patients come for the advanced stage treatment. PTEN inactivation is identified in about 20% of primary prostate tumors in radical prostatectomy and the loss of PTEN is associated with poor clinical and pathological outcomes. The purpose of this study is to prove that there is an association between PTEN expression and risk grade group Gleason prostate adenocarcinoma in Sanglah Public Hospital, Denpasar.Methods: This is a cross-sectional study. The sample size of this study was 35 paraffin blocks. These samples were selected by proportional stratified random sampling from hematoxylin-eosin preparation. Prostate adenocarcinoma was regrouped into 3 categories based on NCCN risk stratification: low risk grade group Gleason (Gleason score ≤ 6), intermediate risk grade group Gleason (Gleason score 7), and high-risk grade group Gleason (Gleason score 8–10). Immunohistochemistry examination of PTEN was performed and the expression was evaluated by scoring method. The data were analyzed by Chi-square and logistic regression.Results: The analysis result showed that there is an association between PTEN expression and risk grade group Gleason that is statistically significant. The loss of PTEN expression associated with higher risk grade group Gleason is of the higher proportion with p=0.001; PR 3.339; 95% CI: 1.296–8.599, but there is no association between the proportion loss of PTEN expression heterogeneously or homogeneously and the risk grade group Gleason with p=0.742; PR 0.663; 95% CI: 0.179–2.457.Conclusions: This study has proved that PTEN expression is associated with higher risk grade group Gleason prostate adenocarcinoma.